The Three Wars of Bernard Lewis. Issue 3 (3rd July 2018) - Kramer, Martin
ABSTRACT: The career of Bernard Lewis was punctuated by three wars: World War II, the Cold War, and what he himself called "the crisis of Islam." The article seeks to demonstrate that for Lewis, these wars formed a continuum, the common thread being the struggle to defend freedom and democracy against the forces of tyranny.